Comparison of the Analgesic Efficacy of Bupivacaine via Wound Catheter with Transdermal Lidocaine Patch for Post Operative Pain Management in Dogs - Bhawsar, Prakhar; Jain, Reshma; Singh Parihar, Atul; Prasad Shukla, Brahm; Shrivastava, Nidhi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Pain management is critical in veterinary care as inadequate relief can lead to stress, immunosuppression, delayed healing and maladaptive  behaviours. Local anaesthetics like bupivacaine and lidocaine play key roles by blocking sodium channels to prevent pain transmission.  Advanced methods, including wound soaker catheters and transdermal patches, provide site-specific, prolonged pain relief. This study,  conducted from May to October 2024, assessed postoperative pain in 12 dogs undergoing tumour excision, amputation and wound  repair. Dogs were divided into two groups: group I (n=6) received 0.5% bupivacaine infiltration every 10-12 h, while group II (n=6)  received 5% lidocaine transdermal patches applied every 24 h. The pain was assessed using the short form of the Glasgow composite  measure pain scale (SF-GCMPS), alongside monitoring hormonal parameter. Results showed that bupivacaine experienced significantly  lower pain scores compared to Group lidocaine, particularly during the early postoperative period. The lidocaine group consistently  demonstrated higher pain scores. Cortisol levels increased significantly in both groups post-recovery, with the bupivacaine group  maintaining the lowest levels at 24 and 48 h postoperatively. The study concluded that bupivacaine infiltration provided superior pain  relief and improved recovery compared to lidocaine patch.
Keywords: Bupivacaine; Post-operative pain management; Transdermal lidocaine patch; Wound catheter